ALTERATIONS IN THE ACETYLCHOLINESTERASE ACTIVITY IN THE BRAIN OF ALBINO MICE EXPOSED TO ACEPHATE - PRASAD, M. SIVA; BABU, K. RAMESH; S. V. RAVIKANTH; P. NARENDER; P. JACOB DOSS (The Bioscan, 2013)
Acephate (AP), a widely available organophosphorus (OP) insecticide, has low mammalian toxicity and is considered non-phytotoxic on many crop plants and therefore it is preferred in agricultural crops. In plants and insects, AP is metabolized extensively to methamidophos (MP), a more potent OP insecticide. The limited mammalian metabolism of AP to MP has been studied in laboratory rat models and suggests that initial formation of MP from AP may inhibit further formation. Hence in the present investigation we have studied the effect of an AP in cholinergic mechanisms in the different regions of brain. For the present study the male mice were exposed to 1/10th LD50 of AP via oral gavage (i.e. 40.5mg/kg body weight). Our results indicate a steady decline of AChE activity in all the regions of the brain of Acephate exposed animals. As expected an increase in ACh activity was noticed in all the regions of the AP exposed animals. We suggest that cholinergic system is seriously affected by the intoxication of Acephate and the effect was more effective in 30 days when compared to 10 days.